1995
DOI: 10.1037/0096-1523.21.5.1053
|View full text |Cite
|
Sign up to set email alerts
|

Search for a conjunctively defined target can be selectively limited to a color-defined subset of elements.

Abstract: In conjunction search, response latencies usually increase with the number of displayed elements, suggesting serial, self-terminating search through all elements. In line with the results of H. Egeth, R. Virzi, and H. Garbart (1984), the present study shows that subjects do not necessarily search all display elements, but can limit their search to a color-defined subset of elements. The results make clear that selective search for a color-defined subset does not depend on saliency of the subset (Experiment 1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
214
5
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(241 citation statements)
references
References 66 publications
21
214
5
1
Order By: Relevance
“…The results obtained by Egeth et al (9) had been corroborated by Kaptein et al (10) . These authors manipulated the size of a to be attended subgroup of stimuli (red lines) and the size of a irrelevant subgroup (green lines).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The results obtained by Egeth et al (9) had been corroborated by Kaptein et al (10) . These authors manipulated the size of a to be attended subgroup of stimuli (red lines) and the size of a irrelevant subgroup (green lines).…”
supporting
confidence: 78%
“…Other evidences had suggested that the search can be restricted to a subgroup of selected stimuli that have a feature in common with the target, for example, the color, the form, the contrast, the movement or the binocular disparity (8)(9)(10)(11)(12) . In the study of Egeth et al (9) , for example, the subjects had been instructed to search for a red O letter located among red Ns and black Os.…”
mentioning
confidence: 99%
“…The results of our first three experiments add to the already available evidence that subjects are very well capable of selecting subsets of visual information on the basis of color (for further evidence, see, e.g., Bundesen, Pedersen, & Larsen, 1984;Bundesen, Shibuya, & Larsen, 1985;Clark, 1969;Francolini & Egeth, 1980;Fryklund, 1975;Humphreys, 1981;Kaptein, Theeuwes, & van der Heijden, 1995;Nissen, 1985;Snyder, 1972;von Wright, 1968von Wright, ,1970von Wright, , 1972. Nevertheless, it is worthwhile to note that our evidence for efficient selection on the basis of color was obtained in a particular situation.…”
Section: Methodsmentioning
confidence: 52%
“…The total number of items within a search display (display size) is manipulated and the search efficiency is examined by the change in response time and/or error rate as a function of display size (see Treisman, 1988;Wolfe, 1998 for a review). However, several previous studies have shown that visual search performance is sensitive to the ratio between the two types of distractors, even when the total number of items in a display remains constant (e.g., Bacon & Egeth, 1997;Egeth et al, 1984;Kaptein et al, 1995;Poisson & Wilkinson, 1992;Zohary & Hochstein, 1989).…”
Section: Distractor-ratio Effectmentioning
confidence: 99%